KOLOIMBA MITH AND THE INCHES RELATIONSHIP IN TOLAKINESS PEOPLE - Jamaluddin Muchtar (Widyariset, 2013)
Indonesian society is rich in myths. However, there are contradictory views among the people who believe and do not believe it. The uncertain truth of a myth followed by human fear of the truth of the myth itself. Myth is not just a mere story, but also cultural phenomenons, a product of human imagination, contain some meanings and social fact believed by the supporters. By taking a case study of Koloimba myth in Tolaki community, Southeast Sulawesi, the study aims to analyze (1) the structure of the myth miteme aspects, (2) the concept of incest in relation to Tolaki cultural myths. The research methods are the techniques of documentation, notes, and interviews. By using the paradigm of Lévi-Strauss’s structuralism, studies show 1. the relation structure Molowu myths and Saweringadi the social structure described through binary oppositions that contain specific messages with the Reject. for example, women><women, 2. the concept of incest in the myth that suggests ban Koloimba mate with a particular individual, is not accompanied by the recommendation, but rather emphasize aspects of the impact of an act that is considered taboo or abstinence done, particularly violations of the prohibition of incest. The results of this study suggest that myths are able deliver moral messages into simple language that guide behaviour and as a means of communication, and supporting the development of knowledge in society.